Dangerous journey - Hunkin, Oliver; Parry, Alan; Bunyan, John, 1628-1688. (Carlisle, Cumbria [Eng] : Candle Books ; Grand Rapids, Mich. : Eerdmans, 1994)
The pilgrim Christian undertakes the dangerous journey to the Celestial City, experiencing physical and spiritual obstacles along the way.
An arrangement of John Bunyan's Pilgrim's progress to accompany the television series Dangerous journey.
Keywords: Christian life -- Juvenile fiction